Housing of the rural population in Ireland - Synnott, Nicholas J. (Statistical and Social Inquiry Society of Ireland, 1906)
It is generally supposed that the question of the housing of agricultural and other labourers in rural districts, which was dealt with in piecemeal and desultory fashion last Session, is now receiving the earnest and considered attention of the Government, and a survey of the position, before this Society, may not be without use.
Read November 27th, 1903.
Keywords: Social housing, Ireland; Farm labourers; Rural housing, Ireland; Housing, Ireland; 314.15